Optimasi Menu Makanan Bagi Pasien Gagal Ginjal Menggunakan Algoritme Lebah - Yeni Herawati; Wayan Firdaus Mahmudy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Kidney failure is a chronic metabolic disease that becomes a health problem in the world. Patients with kidney failure should have a special diet to control their diet and keep the kidney damage from getting worse. Diet to help patients improve eating and sports habits to gain better metabolic control. Patients should limit what foods can be consumed. This causes the patient to really pay attention to the food menu. To solve the case requires a bee algorithm. This study used 132 lists of foods with nutritional content (protein, carbohydrates and fats). The algorithm process uses an integer representation of length 15 which the resulting number represents the food index. From the test, we get the optimal parameter of 100 individuals with the average fitness value of 0.107823, 100 iterations with the average fitness value of 0.103334. The results of this study are the composition of the food menu in a day (breakfast, lunch and dinner) at a minimal cost.